Estabilidade e exigência das vitaminas a-tocoferol, retinol e ácido ascórbico para camarões da espécie Farfantepenaeus subtilis - Pedrosa, Zilmara Vieira (2009)
The carciniculture is an important economic activity for Brazil, basically in the farming of a specific shrimp species (Litopenaeus vannamei). This species has shown in the last years an unsatisfactory performance due to problems caused by illnesses. That has been increasing the interest for the farming of native species like the Farfantepenaeus subtilis which has a better resistance to illnesses, besides being tolerant to several salinity variations they also have an availability of adult females and post larvae and a facility for reproduction in confined places. The nutrition of this species has to be better studied, like the necessities of vitamins A, E and C in these animals s diets. As well as knowing the stability of these vitamins in the processing, storage and handling of this diet. This study consisted of a formulation of eight diets with different levels of vitamins A, E and C and a control diet (with no vitamins). The vitamins were quantified right after the storage period (60 days) to evaluate the losses. The shrimps of the Farfantepenaeus subtilis species were fed with these diets for thirty days, in which it was evaluated the biomass gain and the survival rate. The major vitamin losses were of retinol, α-tocopherol, and ascorbic acid, respectively. The major survival rates (100%) were observed in the R1 and R4 diets which received different levels of vitamin E (184 e 364 UI/Kg), respectively.